PROMISING TECHNOLOGIES WITH ELEMENTS OF AI FOR PROFESSIONAL DEVELOPMENT OF TEACHING - Shyshkina, Mariya; Nosenko, Yuliya (Physical and Mathematical Education, 2023)
Formulation of the problem. Currently, education is going through a difficult stage of modernization caused by the wide spread of digital technologies and the development of Society 4.0. The need to modernize the educational environment of pedagogical institutions, bringing it into line with modern achievements is noted. Solving the tasks of creating a high-tech educational environment in pedagogical institutions is an essential prerequisite for the training of specialists capable of effective use of modern digital technologies in professional activities. Materials and methods. Theoretical methods are applied, in particular, analysis, synthesis, generalization of the regulatory framework, legislative documents, strategies, concepts of Ukraine and foreign countries, research works of Ukrainian and foreign scientists, experts. A prognostic approach is used to determine the ways of further scientific research by direction. Results. The main promising digital technologies, appropriate for use in the professional development of teachers, are considered: cloud computing, immersive technologies, technologies with elements of AI. The trends that currently characterize promising areas of development and use of modern technologies for the personalization of learning are singled out. The prerequisites for achieving the effectiveness of the use of AR/VR are determined, including those ones with elements of AI. Recommendations are provided regarding the use of modern promising technologies, including those ones with elements of AI, for the professional development of teachers. Conclusions. The main difference between the educational systems of the new generation and the previous automated learning tools is a higher level of adaptability. This is achieved by organizing a more flexible and open educational environment using hybrid cloud solutions, AR/VR technologies with elements of artificial intelligence, which provide access to personalized services both individually and collectively. We consider the introduction of digital technologies with elements of artificial intelligence into the educational environment to be a promising direction for improving the training of teaching staff. It is advisable to continue research in the direction of developing appropriate models and methods of designing and using an educational environment with elements of artificial intelligence.